A new species of Ceylonosticta Fraser, 1931 (Odonata: Zygoptera: Platystictidae) from Sri Lanka. Issue 2 (3rd April 2018) - Priyadarshana, Tharaka Sudesh; Wijewardhane, Ishara Harshajith; Peabotuwage, Indika; Jayasooriya, Asanka; Herath, Bimal Eranga
Abstract : A new species of Ceylonosticta from the wet zone of Sri Lanka is described and illustrated, namely Ceylonosticta goodalei sp. nov . (Kuruwita-Erathana foot path, Seethagangula, Adam's Peak, Samanala Nature Reserve, Ratnapura, 6.8196°N, 80.4615°E, 1109 m asl). The species is described from male specimens only and the genital ligula is described and illustrated. Females are as yet unknown. A brief review of Ceylonosticta "species-groups" is provided, provisionally incorporating three recently described species ( C. nancyae, C. rupasinghe, C. alwisi ) as well as C. goodalei . A determination key is updated by addition of these four newly described Ceylonosticta species and now covers 22 endemic species of the genus hereto known from the island. http://www.zoobank.org/urn:lsid:zoobank.org:pub:3A443B9F-CAD0-42AE-A4C1-8476C83DF8E9